Pengaruh Perceived Usefulness dan Perceived Ease of Use terhadap Attitude dan Actual Usage Go-Pay - Gusni Gusni; Ratih Hurriyati; Puspo Dewi Dirgantari (University of Merdeka Malang, 2020)
E-money is one of financial technology (fin-tech) breakthrough that experienced very rapid development in various countries, including Indonesia. One of the most popular is Go-Pay. Go-Pay helps Indonesian people to perform efficiently and effectively transactions without cash, but the fact is that not all Indonesians use its facility. The aim of this paper is to investigate the effect of perceived usefulness and perceived ease of use on the attitude and actual usage of Go-Pay. The unit analysis of this research is an active student of Widyatama University who use Go-Pay with the total sample are 231 respondents by using a nonprobability sampling technique. Path analysis is used to find out variables that have a powerful effect on the attitude and actual usage. The result shows that perceived usefulness and perceived ease of use have a positive effect on attitude, then perceived ease of use and attitude have a positive effect on actual usage. Meanwhile perceived usefulness has a small effect contribution on actual usage of Go-Pay. To increase the actual usage of Go-Pay, perceived easy of use through attitude has a bigger effect contribution compared to perceived ease of use directly on actual usage.https://doi.org/10.26905/jmdk.v8i1.3892